1997
DOI: 10.1103/physrevb.55.4539
|View full text |Cite
|
Sign up to set email alerts
|

Shot noise in resonant-tunneling structures

Abstract: We propose a quantum mechanical approach to noise in resonant tunneling structures, that can be applied in the whole range of transport regimes, from completely coherent to completely incoherent. In both limiting cases, well known results which have appeared in the literature are recovered. Shot noise reduction due to both Pauli exclusion and Coulomb repulsion, and their combined effect, are studied as a function of the rate of incoherent processes in the well (which are taken into account by means of a phenom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 38 publications
7
71
0
Order By: Relevance
“…(11) predicts a maximum suppression of one half of the Poissonian noise (for Γ L = Γ R ), in agreement with the known results [11] for independent particle models.…”
supporting
confidence: 78%
“…(11) predicts a maximum suppression of one half of the Poissonian noise (for Γ L = Γ R ), in agreement with the known results [11] for independent particle models.…”
supporting
confidence: 78%
“…2 are in good agreement with the experimental results obtained by several different groups, with different resonant heterostructures. [12][13][14] Let us mention that scattering (apart from the electron-electron interaction) is not considered here and it can modify present results. In principle, our approach can accurately deal with additional scattering mechanisms by introducing their interaction/potential directly into the Hamiltonian [Eq.…”
mentioning
confidence: 91%
“…Now, let us emphasize the capabilities of our proposal for dealing with the Poisson equation in a QM framework by providing a numerical example. We study the current through a resonant tunneling diode (RTD) which is a quantum-based device that has been exhaustively investigated, both, from theoretical 8,12,13 and experimental 12-14 points of view. We assume a standard GaAs/ AlAs heterostructure system with m = 0.067 m o (m o being the free electron mass).…”
mentioning
confidence: 99%
“…absence of inelastic scattering), and concluded that inelastic processes do not affect shot noise suppression in quantum wells. Later, Iannaccone, Macucci, and Pellegrini [228] solved the master equation allowing explicitly for arbitrary inelastic scattering, and found that the noise suppression factor is given by Eq. (78) at zero temperature for arbitrary inelastic scattering provided the reservoirs are ideal.…”
Section: B Suppression Of Shot Noise In Double-barrier Structuresmentioning
confidence: 99%